Multivariate Studies of Bulb Yield and Morphological Characters in Garlic (Allium sativum L.) Genotypes at Kulumsa, Southeastern Part of Ethiopia - Tsagaye, Dasta; Fufa, Nimona; Wegayehu, Gizaw; Fikre, Demis; Ali, Awoke (International Journal of Bio-resource and Stress Management, 2025)
The experiment was carried out for two consecutive years (2020–2021) from June to October at Kulumsa Agricultural Research Center, Assella, Ethiopia under rain fed conditions using an Alpha lattice design with two replications. One hundred twenty Garlic (Allium sativum L.) genotypes were collected from south eastern parts of Ethiopia, were evaluated for genetic diversity of some morphological and bulb yield characters. The investigated traits included vigor, plant height, neck thickness, shaft length/pseodostem, leaf number plant, leaf width, leaf length, cloves number bulb-1, weight of cloves, clove height, clove diameter and total yield. The cluster mean values showed a wide range of variation for all the traits studied. The chi-square (X2) tests for the six clusters indicate that there are statistically significant differences between all the clusters. The highest inter-cluster distance was recorded between cluster III and VIII (D2=10.90) followed by between cluster III and VII (D2=10.55), One hundred twenty genotypes of garlic were grouped in eleven distinct non- over lapping clusters. The highest number of genotypes were found in cluster I which contained twenty six (26) genotypes, followed by cluster III having twenty one (21) genotypes. From the 12 principal components extracted, the first four principal components (PCs) within an eigenvalue value=>1 explained 65.8% of the total variation among the examined genotypes. Selecting materials should be produced among clusters rather than within clusters for future hybridization breeding efforts.